Building Front-End Rekaruang Application Using Waterfall Development Method in The Design Order Module - Alifia Zahra Firdaus (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Based on research conducted on sixty-ninth-grade female students at Shiraz high school, interior design was able to improve mental health and decrease anxiety and insomnia. This research result shows that the importance of applying interior design to a person's psychological health. However, nowadays, many people do not care about implementing interior design because they are worried if the results are not as desired. It becomes a problem for interior designers in getting customers. Based on these problems, the researcher tries to provide a web-based practical application for bridging interior designers with clients as building owners. This research only focuses on developing Front-End applications using the JavaScript programming language and the vue.js framework. This study applies the waterfall method as a software development method. This research produces a design application that can be a place for interior designers to get clients through design messaging services. This application testing using a user acceptance test. The test results show that three out of five interior designers have accepted the entire process of the design Order service. While the other two designers have accepted conditions for some process on the design Order service to help get clients.